True potatoes seeds (TPS) as an alternative method for potato production in Namibia - Horn, LN; Shimwafeni, Justine; Mulima, Eduardo (Namibian Journal for Research, Science and Technology, 2022)
Potato plays a great role in the human diet all over the world for the achievement of food security program due to its popularity and ability to adopt to different environmental conditions as well as its yielding capacity. Production of potatoes in Namibia hhowever is far less than other countries due to constraints such as unavailability of growing materials in the form of true potato seeds (TPS) or seed tubers. This situation is not only denying the opportuninit for local farmers to produce potato crops but also limiting the oppotunity for Agrobusiness and crop diversification in the country. Without a formal potato seed system farmers will continue making use of varieties of unknown origin as no improved varieties available to the majority of the farmers. Lack of awareness about the use of improved technology and practices has also impeded adoption of potato technologies in Namibia. This review isaiming at to summarizing challenges and constraints to potato Production and value chain in Namibia, and to provide baseline information on potato for current and aspiring producers in Namibia or similar agro-ecologies in Sub-Saharan Africa (SSA).